Information search methods and financial decisions. Issue 4 (30th October 2020) - Bonaparte, Yosef; Fabozzi, Frank J.; Koslowsky, David
Abstract: We investigate whether financial decisions by households are influenced by information search method. The analysis examines Survey of Consumer Finances (SCF) data containing more than 20 information search methods used by households for saving and investment decisions. We classify investors into categories (informal, professional, and comprehensive) based on information search method. We use the 2016 SCF data for our main results; we also use the 1998 SCF to examine the effects of geography and changes in information search over time. We find that information search method influences financial decisions about stock market participation, trading, diversification, risk‐taking, and home bias.